Lessons and prospects of Sino-Russian Arctic cooperation - Jiayu, Bai; Voronenko, Alexandr (Polar Research Institute of China - PRIC, 2016)
The strategic partnership between China and Russia is creating solid ground for the cooperative development of the Arctic. These two states’ joint development of the Northern Sea Route will not only provide additional impulse to the export-oriented economy of China and allow further diversification of supply routes to China, but will also promote investment into the infrastructure and economic growth of Russian northern territories. Climate change in the Arctic has forced China and Russia to acknowledge the sustainable use of the Arctic. On the one hand, exploration of the region should not harm indigenous people’s rights and should help this population improve their standard of living by providing qualified healthcare and opportunities for commercial fulfillment of traditional crafts. On the other hand, this exploration should also include elimination of harmful anthropogenic impact and provide support for environment self-restoration. Sino-Russian Arctic cooperation will help humans discover eco-friendly approaches to use Arctic resources, promote rational use of the Arctic and inspire sustainable development of the region.